Characterization of near tip stresses for a plane-strain off-center crack in a strength mismatched weld. (August 2015) - Kumar, Suranjit; Khan, I.A.; Singh, P.K.; Bhasin, V.; Singh, R.K.
Abstract: The past two decades have seen an increasing emphasis on the development of flaw assessment procedures accounting for the state of stress (constraint) near the crack tip. In-service inspections of many nuclear power plants have revealed that cracks are most likely to occur in a weld or in the regions near the weld. In recent work, the authors have proposed a novel three-parameter scheme to characterize the crack tip opening stress, for small-scale yielding, for a crack lying at the center of a strength mismatched weld. The proposed scheme was validated with detailed finite element analyses using the modified boundary layer formulation. In the present work, the previously proposed scheme is extended to an off-center crack lying in the weld region. Apart from analyzing an off-center crack, studies are performed on an interface crack in a weld having finite width. To validate the proposed scheme, modified boundary layer analyses are carried out for a wide range of offset ratio values (ratio of the crack tip-to-weld center distance to the weld half-width), ranging from 0.33 to 0.9, and strength mismatch ratio values (ratio of yield strength of weld to yield strength of base material), ranging from 0.6 to 1.6. Our studies revealed that the proposed analytical scheme works well for all offset ratios and weld mismatch ratios. For an interface crack, crack tip stresses depend mainly on the strength mismatch ratio between the base and weld material. Practically no significant effect is observed of the weld width on the crack tip opening stress of an interfacial crack. Highlights: A scheme have been proposed to characterize the crack tip stresses for a off-center crack in a strength mismatched weld. The proposed scheme can characterize the radial variation of the crack tip opening stress. Wide range of off-center crack cases in a weld and strength mismatch ratio were considered in studies. For a given strength mismatch ratio, the mismatch induced constraint is maximal for the case of an interface crack.